OC-051 MANAGEMENT OF EPIGASTRIC, UMBILICAL, SPIGELIAN AND SMALL INCISIONAL HERNIA AS A DAY CASE PROCEDURE: RESULTS OF LONG–TERM FOLLOW–UP AFTER OPEN PREPERITONEAL FLAT MESH TECHNIQUE. (13th October 2022) - Zuvela, M; Galun, D; Bogdanovic, A; Bidzic, N; Zivanovic, M; Zuvela, M; Zuvela, M
Abstract: Aim: To investigate short and long-term outcome after the open preperitoneal flat mesh technique (OPPFMT) for umbilical, epigastric, spigelian, small incisional and "port-site" hernia performed as a day case procedure. Materials and Methods: We retrospectively analyzed records of patients who underwent OPFMT for umbilical, epigastric, Spigelian, small incisional and "port-site" hernia. All patients were operated under local anesthesia in ambulatory settings. The operative technique is as follows: polypropylene flat mesh exceeding the size of the hernia defect for 2–3 cm in all directions is placed into a pre-peritoneal position above the intrabdominaly repositioned hernia sac (mesh is placed into hernia sac) and fixed by at least 8 transfascial "U" sutures. Results: In the period from January 2004 to April 2022, 531 patients with ventral hernias (272 with umbilical, 155 with epigastric, 69 with small incisional, 17 with "port site" and 18 with Spigelian hernia) underwent surgery. During the median follow-up of 44 months, 8 (1, 5%) hematomas, 2 (0, 4%) seromas, 2 (0, 4%), superfitial wound infections, 8 (1, 5%) mesh infections and 24 (4, 6%) recurrences occurred. Conclusion: Management of epigastric, umbilical, spigelian and small incisional hernia with OPFMT under local anesthesia as a day case procedure is a safe and associated with favorable long-term outcome.